El dominio fiduciario, los embargos en forma de retención y el deudor cedido - Uribe Mendoza, Diego Alberto (2021)
The trust fund cannot be affected by the debts that the settlor, the trustee, or the beneficiary, —if applicable—, may have before third parties. An order to withhold funds is not effective against assets or rights held in trust as fiduciary ownership. The misinterpretation of tax regulations and the unawareness of the trust institution, not only weakens the confidence in our institutions, but also jeopardizes the reliability of the fiduciary domain over an autonomous estate.